Análise comparativa de dados planialtimétricos obtidos com software QGIS x GNSS RTK em área de estudo da UFSCar - CCA - Santos, John Wesley de Souza (Universidade Federal de São Carlos)
With the advent of technology, geotechnologies have been gaining prominence in recent years, especially in the field of surveying. Currently, there are several ways to perform a topographic survey of a given area, either on-site or remotely, using free software that utilizes satellite imagery. However, each of these systems has technical particularities that can compromise the entire project, given that planimetric and altimetric data obtained on-site or through satellite imagery may present different correspondences. In this sense, the present study aimed to conduct a comparative analysis between planialtimetric data obtained through the QGIS software and GNSS RTK (Real Time Kinematic) technology, in order to evaluate the accuracy, efficiency, and limitations of each approach for topographic surveying. The research was carried out in an experimental area of the Agricultural Sciences Center at the Federal University of São Carlos (UFSCar), using QGIS 3.40.9 for coordinate extraction and a GNSS RTK receiver (CHC NAV) for field data collection. The results showed a high planimetric correspondence between the methods and small altimetric variations, with an average difference of ΔZ = –0.24 m, demonstrating the reliability of GNSS RTK for precision surveys. The most significant discrepancies were attributed to differences in vertical datums and to the resolution of the Digital Elevation Model (DEM) used in QGIS. The integration between GNSS RTK and QGIS proved to be technically feasible and advantageous, combining the centimeter-level accuracy of GNSS positioning with the analytical and visualization tools of the GIS environment. It is concluded that, although QGIS is suitable for preliminary analyses and planning, GNSS RTK offers superior performance in terms of accuracy and reliability. Therefore, the combined use of both platforms constitutes an efficient, precise, and economically viable alternative for topographic surveys applied to agricultural, environmental, and engineering fields.
Comparative analysis of planialtimetric data obtained using QGIS software and GNSS RTK in the UFSCar–CCA study area
Keywords: Geotecnologias; Levantamento planialtimétrico; Levantamento topográfico; Topography; Geotechnologies; Planialtimetric survey; Topographic survey; CIENCIAS AGRARIAS::AGRONOMIA; 9. Indústria, Inovação e Infraestrutura